Phenological Plant Pattern in the Topographic Complex Karstic Landscape of the Northern Dinaric Alps - Aljaž Jakob; Mateja Breg Valjavec; Andraž Čarni (Plants)
Vegetation phenology has lately gained attention in the context of studying human-induced climate change and its effects on terrestrial ecosystems. It is typically studied on various regional and temporal scales. This research focused on the microscale in dolines on the Northernmost part of the Dinaric Alps. The aim was to determine the timing of flowering onset and relate it to topographic and ecological conditions. We studied (1) the floristic gradient along N–W transects divided in 2 m × 2 m plots, from top slopes to the bottom of dolines, and identified discrete groups in relation to this gradient and (2) provided their diagnostic species and communities. The results indicate that the early spring onset of flowering of ground vegetation in the bottom and lower slopes of dolines is stimulated by high spring moisture and nutrient availability, as well as the open canopy of the mesophilous deciduous forests. The flowering onset on the upper slopes and karst plateau starts later, which is due to the precipitation peak in May/June and higher temperatures and light availability of the open canopy of thermophilous deciduous forests. The delayed onset of flowering in late summer in rocky crevices and rocky places is due to a particular physiology stimulated by the harsh site conditions. The phenology pattern along the doline topographic gradient is inverse to general patterns in vegetation phenology. Further study on the role of doline soils should be made to study their impact on phenology.